Programmable one cycle–one disaccharide unit modular synthesis of hyaluronan and chondroitin hybrid glycans. Issue 5 (23rd February 2023) - Li, Shuang; Wang, Shuaishuai; Qu, Jingyao; Han, Jingjun; Yang, Lin; Li, Yi; Li, Lei; Jia, Qingwen; Chen, Congcong; Ling, Peixue; Fang, Junqiang
Abstract : This work develops a robust one cycle–one disaccharide unit method for the assembly of HA–CH hybrid glycans. Abstract : Glycosaminoglycans (GAGs) play critical roles in biological processes via glycan–protein interactions. However, the structure–function relationships of GAGs and glycan-binding proteins are largely unclear due to the lack of structurally well-defined GAGs. Herein, we report a one cycle–one disaccharide unit (OCODU) enzymatic modular assembly strategy for the synthesis of hyaluronan–chondroitin hybrid glycans. With precise employment of glycosyltransferases, a disaccharide could be assembled in one reaction cycle without purification. A total of 66 structures ranging from 6-mer to 14-mer were easily assembled using 5 or fewer cycles with high yields. A glycan microarray containing these structures was fabricated to investigate glycan–protein interactions, revealing that hybrid glycans bind more strongly to hyaladherins than hyaluronans. This synthetic strategy provides an effective catalytic approach for the assembly of polymer glycans with different glycan lengths. In addition, it also promotes the discovery of glycans with high binding activity toward functional glycan-binding proteins.